1986
DOI: 10.1203/00006450-198610000-00086
|View full text |Cite
|
Sign up to set email alerts
|

32 Results of Dietary and Environmental Measures for the Prevention of Atopy in at-Risk Babies: Follow-Up to 3 Years 8 Months of Age

Abstract: Miinchen.Today, it is possible to identify the majority of the newborns with a high risk of atopy by recording family history (FH) and determination of cord-blood IgE (CB-IgE). But this selective screening cannot detect the total number of newborns at risk of atopy. The aim of the present study was to investigate the value of T-cell suppressor count in newborns for the prediction of atopy. We studied CB-IgE, T-cell counts and FH in 138 non-selected newborns. No measures were undertaken for the prevention of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
13
2
Order By: Relevance
“…The results of our studies show that the onset of allergic disease is significantly reduced using the prevention measures. Summing up our studies using a soy-protein formula when breast-milk was not available, we did not see an increased prevalence of soy sensitization [13][14][15][16]. However, other studies failed to show any preventive effect of soy formulae [17,18].…”
Section: Soy-protein Formulaementioning
confidence: 74%
“…The results of our studies show that the onset of allergic disease is significantly reduced using the prevention measures. Summing up our studies using a soy-protein formula when breast-milk was not available, we did not see an increased prevalence of soy sensitization [13][14][15][16]. However, other studies failed to show any preventive effect of soy formulae [17,18].…”
Section: Soy-protein Formulaementioning
confidence: 74%
“…Several studies have emphasized the relationship between CM formula feeding and development of atopic dermatitis (20)(21)(22)(23). The prospective study by Queille-Roussel et al (3) showed that CM formula feeding was an unfavorable fac- tor for the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that soy formulas or breast-feeding supplemented with soy formula for the first six months of life significantly reduce the prevalence of atopic diseases [56][57]. In our studies, using a soy protein formula when breast-milk was not available, we did not see an increased prevalence of soy sensitization [6,7,48,58].However, other studies failed to show any preventive effect of soy formulas [59,60]. These contradictory results may be explained by different factors.…”
Section: Soy-protein Formulasmentioning
confidence: 63%